Leukemia in Ancient Egypt: Earliest case and state‐of‐the‐art techniques for diagnosing generalized osteolytic lesions. (20th February 2019) - Isidro, Albert; Seiler, Roger; Seco, Myriam
Abstract: Malignant bone tumors are uncommon among archaeological skeletal remains, and the general skeletal involvement is even less frequent. Multiple myelomas along with metastases are the most common conditions in paleopathology, whereas malignant myeloproliferative diseases have only been described in a handful of cases. We present a probable case of acute lymphocytic leukemia in a skeleton of an individual from Ancient Egypt, dated to the end of the First Intermediate Period and the beginning of the Middle Kingdom (c 2160–2000 bc ). The excavation of the Temple of Millions of Years of Thutmosis III located in el‐Assasif (Luxor, Upper Egypt) recovered a total of 41 complete individual from an associated grave‐Necropolis placed close to the north enclosure wall. The individual, a 16 to 21‐year‐old male, showed a severe disease affecting all the skeleton with, predominantly, osteolytic lesions and areas of new bone formation. Gross examination under magnification and X‐ray in field were performed. We review the paleopathological literature to compare the cases previously reported of malignant disease. The morphology and distribution of the lesions of the individual are discussed to make an adequate differential diagnosis in the individual. Several criteria suggest that the disease was most likely acute lymphocytic leukemia: The individual died before the age of 21, the patterns of the bone lesions as well as its distribution below the elbow and knee joints, the presence of a gap in the coronal suture, and the mandible involvement. If this is the case, it would be the oldest case of leukemia described in Ancient Egypt and could help to understand the evolution patterns of cancer in the history.